Comparative Financial Health Analysis of Co-operative Milk Processing Plants in Ahmednagar District of Maharashtra - B. Gawali, Prof. Ravindra; Gadekar, Dr. Ashutosh (IJRDO - Journal of Business Management, 2017)
This paper aims at analyzing and comparing the financial health trends of cooperative milk processing plants in Ahmednagar district of Maharashtra using Altman Z score analysis. The two milk processing plants selected on the basis of simple random sampling method out of 14 milk cooperative milk processing plants. The researcher used quantitative methodology as financial ratios are calculated from the analysis of financial statements of milk processing plants over a period of 12 years during 2001 -2012. Statistical t-test taken to compare the mean differences of two cooperative plants to determine whether there is significant difference between the financial healths’s of two sampled milk processing plants. Through hypothesis test it is statistically inferred that both the milk processing plants are too much in a healthy position. The study concluded that Milk processing plants are financially healthy and predicted not to be in financial difficulty in next two years as per Z Score model. The study suggested that the financial executives of milk processing plants needs to manage the financial position well as over the 12 years period during 2001-2012, the milk processing plants shows decreasing trends in Z score